prompt
stringlengths
46
55
ground_truth
int64
-10
10
Solve for a in the following equation: -7a + 1 = 15
-2
Solve for z in the following equation: -1z - 7 = -14
7
Solve for x in the following equation: 3x = -30
-10
Solve for z in the following equation: 6z = -54
-9
Solve for x in the following equation: 9x + 4 = 58
6
Solve for b in the following equation: -6b + 8 = 32
-4
Solve for b in the following equation: 5b + 6 = 16
2
Solve for z in the following equation: 3z - 8 = 19
9
Solve for z in the following equation: 4z + 5 = -27
-8
Solve for y in the following equation: -8y - 6 = -70
8
Solve for x in the following equation: -4x = -16
4
Solve for a in the following equation: -7a + 2 = -47
7
Solve for x in the following equation: 9x + 2 = 38
4
Solve for x in the following equation: -1x - 6 = -9
3
Solve for x in the following equation: -3x + 4 = 10
-2
Solve for y in the following equation: -4y - 3 = -31
7
Solve for b in the following equation: -5b - 4 = 36
-8
Solve for x in the following equation: 2x + 6 = 4
-1
Solve for c in the following equation: -6c + 2 = -40
7
Solve for z in the following equation: 2z + 3 = -3
-3
Solve for x in the following equation: 7x + 3 = 66
9
Solve for b in the following equation: 3b - 4 = -28
-8
Solve for z in the following equation: 3z + 5 = -22
-9
Solve for b in the following equation: -2b + 8 = -8
8
Solve for y in the following equation: 8y = -80
-10
Solve for z in the following equation: 7z - 6 = 1
1
Solve for x in the following equation: 8x + 3 = -37
-5
Solve for y in the following equation: 5y - 7 = -42
-7
Solve for c in the following equation: -1c - 7 = 1
-8
Solve for x in the following equation: -7x + 2 = 37
-5
Solve for y in the following equation: -4y + 4 = -12
4
Solve for a in the following equation: -6a + 3 = 27
-4
Solve for c in the following equation: 8c - 1 = 63
8
Solve for x in the following equation: 5x - 5 = -45
-8
Solve for b in the following equation: -9b - 9 = 63
-8
Solve for x in the following equation: -3x - 5 = -32
9
Solve for c in the following equation: 4c - 8 = -12
-1
Solve for a in the following equation: -7a - 7 = 63
-10
Solve for x in the following equation: 3x = -15
-5
Solve for c in the following equation: 7c + 9 = -12
-3
Solve for z in the following equation: -5z + 5 = 45
-8
Solve for z in the following equation: 10z - 4 = -64
-6
Solve for a in the following equation: -2a + 6 = -14
10
Solve for c in the following equation: 6c + 10 = 28
3
Solve for a in the following equation: -6a - 3 = -21
3
Solve for b in the following equation: 4b - 6 = 18
6
Solve for z in the following equation: 1z - 5 = -8
-3
Solve for a in the following equation: -6a + 7 = -47
9
Solve for z in the following equation: 10z - 6 = 24
3
Solve for x in the following equation: -2x + 6 = 18
-6
Solve for a in the following equation: 3a - 4 = 20
8
Solve for x in the following equation: -9x + 2 = 56
-6
Solve for x in the following equation: -3x - 1 = -7
2
Solve for z in the following equation: -8z + 5 = -75
10
Solve for z in the following equation: 6z + 10 = 34
4
Solve for y in the following equation: -10y - 1 = -1
0
Solve for x in the following equation: -5x - 8 = 22
-6
Solve for a in the following equation: 2a - 7 = 13
10
Solve for b in the following equation: -4b + 3 = 27
-6
Solve for a in the following equation: 7a - 1 = 13
2
Solve for b in the following equation: 4b + 5 = -31
-9
Solve for x in the following equation: 4x - 5 = -9
-1
Solve for y in the following equation: -2y - 1 = 3
-2
Solve for y in the following equation: -6y - 1 = 59
-10
Solve for b in the following equation: 9b - 8 = 10
2
Solve for y in the following equation: -6y + 6 = 18
-2
Solve for x in the following equation: -7x + 3 = -53
8
Solve for c in the following equation: -5c + 1 = -44
9
Solve for y in the following equation: -2y - 5 = -9
2
Solve for x in the following equation: 4x + 10 = 50
10
Solve for z in the following equation: 8z - 3 = 5
1
Solve for c in the following equation: -4c = 20
-5
Solve for y in the following equation: -10y + 4 = 44
-4
Solve for x in the following equation: 9x - 2 = -47
-5
Solve for b in the following equation: -3b - 5 = -5
0
Solve for y in the following equation: 2y - 6 = -2
2
Solve for x in the following equation: 1x + 4 = 6
2
Solve for y in the following equation: -5y + 1 = -49
10
Solve for a in the following equation: -7a + 8 = 1
1
Solve for b in the following equation: -5b - 4 = 16
-4
Solve for x in the following equation: -3x - 2 = -2
0
Solve for y in the following equation: -7y - 10 = -45
5
Solve for a in the following equation: -7a - 6 = 8
-2
Solve for c in the following equation: 4c - 10 = 2
3
Solve for a in the following equation: 6a + 9 = 51
7
Solve for c in the following equation: -8c - 3 = -19
2
Solve for x in the following equation: -6x - 5 = -53
8
Solve for y in the following equation: 2y + 10 = 26
8
Solve for a in the following equation: -2a - 3 = -19
8
Solve for z in the following equation: 4z - 8 = -16
-2
Solve for a in the following equation: 2a - 2 = -18
-8
Solve for a in the following equation: 4a - 4 = -40
-9
Solve for b in the following equation: 3b + 3 = 27
8
Solve for x in the following equation: -1x + 1 = -9
10
Solve for b in the following equation: -2b - 6 = 14
-10
Solve for b in the following equation: -10b + 9 = 109
-10
Solve for c in the following equation: 3c + 6 = 30
8
Solve for z in the following equation: 2z - 6 = -4
1
Solve for a in the following equation: -3a - 1 = -1
0
Solve for y in the following equation: 9y - 4 = -76
-8
README.md exists but content is empty.
Downloads last month
19